REIMAGINING EDUCATION THROUGH AI CHATBOTS: INNOVATION AND IMPLICATIONS - Desai, Darshana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence (AI) chatbots are fundamentally reshaping modern education by offering scalable, personalized learning and automating administrative workflows. This paper presents a comprehensive review of peer-reviewed research from 2016 to 2024, evaluating the capabilities, advantages, limitations, and ethical concerns associated with AI-powered conversational agents in diverse educational settings. The findings reveal that AI chatbots hold significant promise for improving student engagement, tailoring instruction to individual needs, and enabling 24/7 support. However, challenges remain, including insufficient emotional intelligence, potential biases in training data, risks to student data privacy, and issues related to the integration of chatbots into legacy Learning Management Systems (LMS). To maximize their benefits and mitigate these limitations, future research and development should prioritize the creation of emotionally aware, contextually adaptive, and ethically governed chatbot systems. This paper also provides practical recommendations for educators, researchers, and policymakers committed to fostering inclusive, effective AI-enhanced classrooms.